2014
DOI: 10.1093/gastro/gou026
|View full text |Cite
|
Sign up to set email alerts
|

Radiographical evaluation of ulcerative colitis

Abstract: Radiographical modalities have become important diagnostic tools in cases of ulcerative colitis (UC). Imaging can be used non-invasively to determine the extent of involvement, severity of disease and to detect disease-related complications and extra-intestinal inflammatory bowel disease (IBD) manifestations. While abdominal X-rays and barium enemas still retain their relevance in specific clinical settings, the use of computed tomography enterography (CTE) or magnetic resonance enterography (MRE) are now used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 60 publications
0
26
0
3
Order By: Relevance
“…Some of the studies have shown a significant difference between colon wall thickness among cases with moderate to severe colitis and cases of mild or inactive colitis either before or after treatment. 24,25 In our study the mural thickness of colon among new cases of UC (6.4±1.3mm) was significantly more than this value in cases who diagnosed as UC flare(5.5±1.7mm, P=0.02). Moreover average thickness of colon wall in active or new cases of UC (average 5.9, range 2-9mm) was significantly more than mural thickness in control group (average 3.3, range 3-4mm).…”
Section: Discussionmentioning
confidence: 40%
“…Some of the studies have shown a significant difference between colon wall thickness among cases with moderate to severe colitis and cases of mild or inactive colitis either before or after treatment. 24,25 In our study the mural thickness of colon among new cases of UC (6.4±1.3mm) was significantly more than this value in cases who diagnosed as UC flare(5.5±1.7mm, P=0.02). Moreover average thickness of colon wall in active or new cases of UC (average 5.9, range 2-9mm) was significantly more than mural thickness in control group (average 3.3, range 3-4mm).…”
Section: Discussionmentioning
confidence: 40%
“…Cross-sectional images of patients reveal the type and extent of their intestinal inflammation. The location and degree of inflammation and wall thickening determines the manifestation of IBD [118]. Further, these factors are heavily considered when diagnosing patients with IBD as opposed to other diseases.…”
Section: Computed Tomographymentioning
confidence: 99%
“…Technetium-99-m hexamethyl-propyleneamine oxime (99mTc-HMPAO) labeled white blood cell scintigraphy is an imaging technique that employs radioactive isotopes to detect active inflammation [34] . It may be used in IBD to assess disease activity, but due to limited availability and high cost, it is not routinely performed.…”
Section: Nuclear Medicine Imagingmentioning
confidence: 99%